(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
The use of innovative teaching methodologies is crucial in enhancing English language learning outcomes among students. One such approach is the incorporation of jigsaw reading activities, which promote active engagement, collaboration, and critical thinking skills. This article explores the efficacy of jigsaw reading activities in English language classrooms and examines their impact on students’ language proficiency, comprehension, and motivation. Through a review of existing literature and empirical evidence, this study sheds light on the benefits of implementing jigsaw reading activities and provides practical insights for educators seeking to enhance their teaching practices.